SITEM PENDUKUNG KEPUTUSAN PEMILIHAN DOSEN TERBAIK DI STMIK PRINGSEWU DENGAN MENGGUNAKAN METODE VIKOR - Ningsih, Fitri; Trisnawati, Trisnawati (JECE (Journal of Ethics and Character Education), 2023)
The role of lecturers in learning at a university is a very important part and effects the quality of students that will be produced. The task of a lecturer is to plan, implement the learning process, as well asassess and evaluate learning out comes. The selection of the best lecturers will make it easier for us to know the performance. of allecturer inccollege. Decision support system is one of the alternatives used in selecting the best lecturers. This study uses the Visekriterijumsko Kompromisno Rangiranje (VIKOR) method using seven criteria, including length of service, achievements, research, journals, academic positions, community service, and student assessments. And has four alternatives, namely Lecturer 1, Lecturer 2, Lecturer 3, and Lecturer 4. The final result of the research shows that the selection of the best lecturer at STMIK Pringsewu with the highest-ranking result is alternative 4 or A4 with the largest result, namely 0,75